Fish Community Structure in Karangkates Reservoir Malang Regency East Java - Damayanti, Dienda Happy; Latuconsina, Husain; Prasetyo, Hamdani Dwi (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
Karangkates Reservoir is a reservoir formed due to the damming of the flow of the Brantas River and the supply of rainwater, has various benefits as a flood prevention, power plant, water supply for agricultural irrigation needs, for fisheries activities. This reservoir is also utilized by local fishermen for fisheries activities, both capture fisheries and aquaculture activities. This study aims to determine the structure of the fish community which includes diversity, uniformity, dominance and water quality of Karangkates reservoir. This study used a survey method with a sampling technique of